Efficacy of deoxyspergualine for antibody-mediated rejection and proteinuria after kidney transplantation - Hideki Ishida; Kazunari Tanabe (Dove Medical Press, 2008)
Hideki Ishida, Kazunari TanabeDepartment of Urology, Tokyo Women’s Medical University, Tokyo, JapanAbstract: A patient showing antibody-mediated rejection (AMR) with severe vasculitis, and massive proteinuria after kidney transplantation was treated with deoxyspergualine (DSG, Spanidin®, Nippon Kayaku). DSG showed marked efficacy for this patient’s symptoms. We report on a patient for whom DSG was effective against AMR after renal transplantation.Keywords: deoxyspergualine (DSG), vascular rejection, antihuman leukocyte antigen (HLA) antibody